2023
DOI: 10.1002/hsr2.1740
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between ARISCAT risk score and cardiopulmonary exercise test values in risk prediction of postoperative pulmonary complications of major abdominal surgeries in a tertiary cancer hospital: A cross‐sectional study

Somaye Rezaian,
Mehrnaz Asadi Gharabaghi,
Besharat Rahimi
et al.

Abstract: Background and AimsPulmonary complications are common after surgery. They include vascular thrombosis, pneumonia, respiratory failure (RF), and pain‐related atelectasis. There are a number of models to predict the risk of postoperative respiratory events other than thrombosis. The aim of this study was to explore the correlation of assess respiratory risk in surgical patients in Catalonia (ARISCAT) scoring and cardiopulmonary exercise test (CPET) values in prediction of postoperative pulmonary complications (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…In adults undergoing major abdominal cancer surgeries, Rezaian et al found that VO 2 max was significantly lower (11.9 vs. 16.8 mL/kg/min, p < 0.0001) in patients who developed postoperative respiratory failure. Alone, CRF had a low to moderate correlation with the ARISCAT pulmonary risk score [50]. In a recent meta-analysis, Steffens et al found that a higher VO 2 max was strongly associated with improved outcomes in adults undergoing cancer surgery [51].…”
Section: What Is the Rationale Of Prehabilitation In Cancer Patients?mentioning
confidence: 99%
“…In adults undergoing major abdominal cancer surgeries, Rezaian et al found that VO 2 max was significantly lower (11.9 vs. 16.8 mL/kg/min, p < 0.0001) in patients who developed postoperative respiratory failure. Alone, CRF had a low to moderate correlation with the ARISCAT pulmonary risk score [50]. In a recent meta-analysis, Steffens et al found that a higher VO 2 max was strongly associated with improved outcomes in adults undergoing cancer surgery [51].…”
Section: What Is the Rationale Of Prehabilitation In Cancer Patients?mentioning
confidence: 99%